PENGARUH CITRA MEREK, HARGA PRODUK BUTTONSCARVES TERHADAP KEPUTUSAN MINAT BELI MAHASISWA UNIVERSITAS PELITA BANGSA - wahyuningsih, sri wahyuningsih (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
This research aims to determine the influence of the Mere Image of Buttonscarves products on demand to buy and the price of Buttonscarves products on buying interest of Pelita Bangsa University Students. The Population in this study were Pelita Bangsa University students in Cikarang. The sampling technique used is validity and reliability. Data were analyzed using classic assumption testing techniques, multiple linear regression anallsis. The results of this research show that there is a positive and significant influence between price on buyinginterst and a positive influence between brand image on buying interest. The results of this research show that brand image and product price have a positive influence on purchase intention.